If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = sqrt(2x + 1) Multiply f * x fx = sqrt(2x + 1) Reorder the terms: fx = qrst(1 + 2x) fx = (1 * qrst + 2x * qrst) fx = (1qrst + 2qrstx) Solving fx = 1qrst + 2qrstx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = qrstx-1 + 2qrst Simplifying f = qrstx-1 + 2qrst Reorder the terms: f = 2qrst + qrstx-1
| -1÷2/4= | | 9x-8(x-9)+7(y-9)= | | 12x^2-24x+12= | | -1÷2/4 | | 8x-14=8x | | (9ab/10b^3)*(2b/3a) | | b2-4/2=10 | | 4/5x-214 | | m^2-4m=5m-8 | | 13/m=2/9 | | 8(4x+4)=-5x-32 | | 6+4=(6x+9)/3 | | 7x-28=7(x-3) | | x(5y)=5xy | | 2ln(y+2)-ln(y+6)=0 | | 20x^4=12 | | 8n+7=17 | | T=-390xn | | In(6)+ln(5x-10)=ln(11) | | X^2+35x-20=0 | | 9x+8=7x+24 | | x^5-2x^4-x^3=0 | | 5xy+2x=0 | | 5-3(x-4)=5 | | (x-24)(5x-1)=0 | | -4x+3=y | | 3w-3=-9 | | 13x=6x^(1/2) | | 13x=6x^1/2 | | v=-2000t | | -3V-(7/2)=(2/5)V-(3/5) | | -3V-7/2=2/5V-3/5 |